Meningkatkan Kepuasan Nasabah Melalui Pelayanan Prima di Bank BRI Padang Harapan: Meningkatkan Kepuasan Nasabah Melalui Pelayanan Prima di Bank BRI Padang Harapan - Des Wahyudi, Egro; Eko Sumartono; Mujiono; Rika Dwi Yulihartika (Dharmakayana, 2025)
This study aims to analyze the impact of service quality on customer satisfaction at Bank BRI Padang Harapan Unit, Bengkulu City. The research employed a descriptive qualitative approach through participatory observation and semi-structured interviews with employees and customers during a one-month field internship. The findings indicate that service responsiveness, adoption of digital technology (BRImo), and effective communication are key factors in improving customer satisfaction and loyalty. The study also identifies several service quality improvement strategies, including human resource training, customer education, and digital service promotion. The primary contribution of this research lies in applying a digital approach within the context of local banking services.